PRAGMATIC POTENTIAL AND PRAGMATIC ADAPTATION IN THE TRANSLATION OF FICTION: A CROSS-CULTURAL PERSPECTIVE (Journal of Universal Science Research, 2025)
This article examines the roles of pragmatic potential and pragmatic adaptation in fiction translation, focusing on their contributions to creating culturally relevant and resonant target-language texts. Pragmatic potential involves the interpretative flexibility that translators utilize to preserve communicative intent and cultural nuance, while pragmatic adaptation involves specific modifications to enhance comprehension and relevance for the target audience without compromising the original’s impact. Using theories from Eugene Nida, Lawrence Venuti, Mona Baker, and Ernst-August Gutt, this article reviews practical case studies to illustrate how these strategies facilitate successful meaning transfer. The study highlights how translators function as cultural mediators, fostering cross-cultural understanding and the dynamic exchange of ideas through literary translation.